Differences in the amplitude of X-cell responses as a function of depth in layer A of lateral geniculate nucleus in cat. - Bowling, D B (1987)
1. Extracellular recordings were made from 131 X-like cells (hereafter called X cells) at different depths in layer A of the lateral geniculate nucleus (l.g.n.) in the cat. The depths of the cells were measured accurately by orienting the electrodes parallel to the borders of the layer and reconstructing the electrode tracks from histological sections. 2. Each cell was stimulated with a standardized stimulus; a 500 ms, low-contrast (10%) spot of light, matched in size to the centres of the receptive fields. The responses were later compared with the depths of the cells in the layer. 3. The amplitudes of the responses, which ranged between peak values of 20 and 400 spikes/s in different cells, were related to the depths of the cells in the layer. On average, the response amplitudes of the X-on cells near the borders of the layer were small compared to those in the middle. The responses of the X-off cells were reciprocal; large near the borders of the layer and small in the middle. 4. The results reveal a sublaminar organization in layer A based on the signs and amplitudes of X-cell responses. It is suggested that the pattern reflects differences in signalling within the X-on and X-off channels that are preserved in the relay to the visual cortex.